Interpretive approaches to global climate governance (de)constructing the greenhouse - Methmann, Chris 1981- (Routledge, 2013)
Global climate change is perceived to be one of the biggest challenges for international politics in the 21st century. This work seeks to fuse a global governance perspective together with different interpretive approaches, offering a novel way of looking at international climate politics. Equipped with a common interpretive tool-kit, the authors examine different issue-areas and excavate the contours of an overall pattern - the depoliticisation of climate governance. It is this concept which represents the overarching theme connecting the different contributions, addressing issues such as
Keywords: Governance; Globalisierung; Nachhaltigkeit; Umweltpolitik; Klima